Best Proximity Pairs for Upper Semicontinuous Set-Valued Maps in Hyperconvex Metric Spaces. (5th November 2008) - Amini-Harandi, A.; Farajzadeh, A. P.; O'Regan, D.; Agarwal, R. P.
Abstract : A best proximity pair for a set-valued mapF : A ⊸ B with respect to a mapg : A → A is defined, and new existence theorems of best proximity pairs for upper semicontinuous set-valued maps with respect to a homeomorphism are proved in hyperconvex metric spaces.